Pre-emptive administration of intravenous acetaminophen with transversus abdominis plane block (tap-blocke) in the prevention of fentanil-induced hyperalgesia in pediatric oncological patient undergoing abdominal surgery - Dmytriiev, Dmytro; Nazarchuk, Oleksandr (Journal of Education, Health and Sport, 2015)
Dmytriiev Dmytro, Nazarchuk Oleksandr. Pre-emptive administration of intravenous acetaminophen with transversus abdominis plane block (tap-blocke) in the prevention of fentanil-induced hyperalgesia in pediatric oncological patient undergoing abdominal surgery. Journal of Education, Health and Sport. 2015;5(10):98-107. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32514 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A98-107 https://pbn.nauka.gov.pl/works/659929 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. UDC: 616-089.5-053.2: 616-006 PRE-EMPTIVE ADMINISTRATION OF INTRAVENOUS ACETAMINOPHEN WITH TRANSVERSUS ABDOMINIS PLANE BLOCK (TAP-BLOCKE) IN THE PREVENTION OF FENTANIL-INDUCED HYPERALGESIA IN PEDIATRIC ONCOLOGICAL PATIENT UNDERGOING ABDOMINAL SURGERY Dmytro Dmytriiev, Oleksandr Nazarchuk Department of Anesthesiology and Intensive care, Vinnytsya National Pirogov Memorial Medical University Abstract Background: Acetaminophen is a selective COX-2 agonist that has been shown to decrease the intensity of opioid-induced hyperalgesia (OIH) in children. We aimed to investigate the effects of preemptive administration of intravenous acitomenofen in the prevention of high-dose fentanil-induced hyperalgesia in pediatric patients. Methods: 45 patients of American Society of Anesthesiologists physical status 1-3 undergoing abdominal surgery were randomly assigned to one of the following three groups. each of which received either IV acetaminophen (an initial dose of 1.5 ml/kg for 40 min before before the induction of anesthesia) or placebo saline 40 min before the induction of anesthesia and intraoperative fentanil infusion: group LFH received a placebo and 0.05 μg/kg/min fentanil; group FH received a placebo and 0.3 μg/kg/min fentanil; and group AFH received IV preemptive administration acetaminophen and TAP-blocke bupivacaine 0,3 mg/kg. Results: The mechanical hyperalgesia threshold 12 hr after surgery was significantly lower in group FH than in the other two groups. Postoperative pain intensity using visual analog scale (VAS) and cumulative volume of a patient controlled analgesia (PCA) containing morphine over 12 hr were significantly greater in group FH than in group AFH. The time to the first postoperative analgesic requirement was significantly shorter in group RH than in the other two groups. The sevoflurane requirement was significantly greater in group LFH than in the other groups. The frequency of hypotension and bradycardia was significantly higher, but shivering and postoperative nausea and vomiting were significantly lower in group AFH than in the other two groups. Conclusions: High-doses of fentanil induced hyperalgesia, which presented a decreased mechanical hyperalgesia threshold, enhanced pain intensity, a shorter time to first postoperative analgesic requirement, and greater morphine consumption, but IV preemptive administration acetaminophen alleviated those symptoms. IV preemptive administration acetaminophen may be an effective treatment option for preventing or attenuating OIH. Key words: IV preemptive administration acetaminophen, Opioid-induced hyperalgesia, fentanil, TAP-blocke.